Intestinal perforation following allogeneic stem cell transplantation caused by Epstein-Barr virus-positive mucocutaneous ulcer - Klaus Hirschbühl; Tina Schaller; Bruno Märkl; Adriana Amerein; Michael Gebhard; Georg Braun; Susanne Wasserberg; Elisa Sala; Martin Trepel; Christoph Schmid (Haematologica)
Not available.